POTENSI ANTIOKSIDAN EKSTRAK METANOL DIATOM Amphora sp. - Ach. Khumaidi; Astik Umiyah; Abdul Muqsith; Abdul Wafi (Universitas Sriwijaya, 2021)
Diatoms are a type of microalgae with a quite strong potential in the health sector as antioxidants, anticancer, and antivirals. But until now in Indonesia is still very rarely carried out research on the antioxidant potential of diatoms. The purpose of this study was to determine the antioxidant potential of Amphora sp. extracted with methanol. The method used in the extraction process is maceration, with a ratio of sample and methanol 1: 3 (300 g: 900 ml). The evaporation process compacted maserate resulting from maceration, then analyzed the total chlorophyll content, total flavonoids, and total phenols. Amphora sp. extraction results showed good potential with 7.08 ppm chlorophyll content, total flavonoids 6,299 ppm, and total phenol 7,085 ppm, and IC50 DPPH values of 3332.5 ppm. The IC50 value of the extract of Amphora sp. still classified as very weak antioxidant activity, but in general the extract of Amphora sp. has other bioactive potentials such as chlorophyll, flavonoids, and total phenol which can be used as material for further studies for the development of natural medicinal ingredients from Amphora sp.Key words: antioxidant, diatome, DPPH, macaration, methanol.